Item Response Models in Psychometrika and Psychometric Textbooks - Kim, Seock-Ho; Kwak, Minho; Bian, Meina; Feldberg, Zachary; Henry, Travis; Lee, Juyeon; Ölmez, İbrahim Burak; Shen, Yawei; Tan, Yanyan; Tanaka, Victoria; Wang, Jue; Xu, Jiajun; et al. (Frontiers in Education, 2020)
Item response theory modeling articles from 83 years of Psychometrika are sorted based on the taxonomy by Thissen and Steinberg (1986). Results from 377 research and review articles indicate that the usual unidimensional parametric item response theory models for dichotomous items were employed in 51 per cent of the articles. The usual unidimensional parametric item response theory models for polytomous items were employed in 21 per cent of the articles. The multidimensional item response theory models were employed in 11 per cent of the articles. Item response theory models from the selected psychometric textbooks are also reviewed and contrasted with those from Psychometrika to explore the instructional use of various item response models. A new classification based on data types is proposed and discussed.